A Cobweb Model of Financial Stability in Norway - Geir Arne Dahl; Thea Birkeland Kloster; Unni Larsen; Ketil Johan Rakkestad; Rebekka Reisvaag; Bjørne Dyre H. Syversten; Cathrine Bolstad Træe (Norges Bank, 2011)
The Staff Memo presents a cobweb model of financial stability in Norway. The model is a technical tool that incorporates both vulnerabilities in the banking sector and external risks to the banking sector. Thus, the model helps us analyse financial stability in a more systematic manner. As the model assigns scores to vulnerabilities and risks based on historical evidence, it improves our perception of the state of the financial system. Coupled with a graphical presentation along several dimensions, the model is expected to enhance communication of our assessment of financial stability. The cobweb model performs reasonably well during periods of financial distress. Some of the indicators seem to signal the build-up of financial imbalances, while others are of a more contemporaneous nature. Judgment was used to decide on the final positioning of some of the indicators. As each crisis is different, no model can encompass all the relevant factors. In such cases, the indicators should be evaluated with the goal of improving them. If further development of the cobweb model is neither feasible nor appropriate, a subjective adjustment is undertaken based on other available information. Overruling the raw outcome of the model is documented in the Financial Stability report.
hdl:11250/2507320
Keywords: 330